2020
DOI: 10.1016/j.cgh.2019.02.044
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Risk of Serious Infections With Biologic and/or Immunosuppressive Therapy in Patients With Inflammatory Bowel Diseases: A Systematic Review and Meta-Analysis

Abstract: This article has an accompanying continuing medical education activity, also eligible for MOC credit, on page e7. Learning Objective-Upon completion of this activity, successful learners will be able to list the relative risk of serious infection with various treatment strategies in patients with inflammatory bowel disease; and in addition to biologic and immunomodulator therapies, list risk factors for serious infections in patients with inflammatory bowel diseases. BACKGROUND & AIMS: We performed a systemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
98
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(109 citation statements)
references
References 43 publications
4
98
0
7
Order By: Relevance
“…One of the RA patients was treated with Methotrexate during the entire period of hospitalization, and her condition remained stable. According to a study, coadministration of Methotrexate and Hydroxychloroquine did not result in an increased risk of hospitalization due to infection [7]. In the present report, a 79-year-old male patient with SSc progressed to critical COVID-19, and this may be explained by The texture of both lungs is disordered, the transparency is increased, some of them have reticular changes, multiple patchy ground glass density shadow and fuzzy edge are seen in both lungs.…”
Section: Discussionsupporting
confidence: 47%
“…One of the RA patients was treated with Methotrexate during the entire period of hospitalization, and her condition remained stable. According to a study, coadministration of Methotrexate and Hydroxychloroquine did not result in an increased risk of hospitalization due to infection [7]. In the present report, a 79-year-old male patient with SSc progressed to critical COVID-19, and this may be explained by The texture of both lungs is disordered, the transparency is increased, some of them have reticular changes, multiple patchy ground glass density shadow and fuzzy edge are seen in both lungs.…”
Section: Discussionsupporting
confidence: 47%
“…Several immunotherapies in patients with IBD have been associated with an increased risk of infections as they may inhibit intracellular signalling cascades needed for the host to fight pathogens. [55][56][57] Corticosteroids, for instance, are potentially associated with an increased risk for infections and have been widely used in studies from China for treatment of ARDS and hyperinflammation in covid-19. Although these studies were not designed to evaluate the effects of steroids, one study even suggested that treatment with methylprednisolone decreases the risk of death in covid-19.…”
Section: Immunotherapy In Ibd: Potential Effects On Covid-19mentioning
confidence: 99%
“…Anti‐TNF agents have been shown to increase the risk of upper and lower respiratory tract infections, as well as serious and opportunistic pulmonary infections 62,75,76 . Compared with anti‐TNF monotherapy, risk of serious infections increases with combination of anti‐TNF and an immunosuppressive agent or most significantly in combination with corticosteroids 77 . In a study that did not separate mono—or combination—anti‐TNF therapies, the risk of pneumonia was only slightly increased in patients receiving a TNF antagonist (OR: 1.28, 95% CI [1.08‐1.52]) 62 …”
Section: Management Of Immunosuppression With Covid‐19mentioning
confidence: 99%